Geoelectric investigation of hot springs in Maharashtra - Gupta, Gautam; Erram, Vinit C.; Maiti, S. (My University, 2010)
Thermal springs are the surface manifestations of the subsurface geothermal energy which has attained significant attention in recent years as an alternated energy source. The state of Maharashtra in India is characterized by superficial thermal manifestations represented by numerous hot springs, mostly restricted in the western coast. An attempt is made here to study the possible geothermal sources and to establish the subsurface structure and aquifer system over three hot springs in Ratnagiri district in western Maharashtra based on the analysis of vertical electrical resistivity soundings (VES). Resistivity contouring has been carried out for different electrode spacing i.e. AB/2=5m, 15m, 30m, 50m and 100m which provides the variation of resistivity at five different horizons. A low apparent resistivity of the order of 10-40 Ω-m is prominent at shallow depth of 5m (between 17.2 to 17.25 latitude), which coincides with the location of Tural hot spring. This conducting feature is also observed at other depths. It is also evident that the low resistivity at Tural is spreading as the depth increases. It is possible that the thermal spring source at Tural is located at greater depths. The Aravali hot spring is characterized by a minor low apparent resistivity at all the depths indicating that this is weak compared to the Tural spring. The Tural spring is much hotter than the Aravali one at the surface along with gas emission. The 2-D geoelectrical sections delineated the geometry of the aquifer bodies associated with the hot springs. A close grid magnetic study will further elucidate the geothermal resources and delineate the structural setting of the area.
Keywords: Resistivity; Hot spring; Aquifer; Maharashtra western